Effect of low-level laser therapy on angiogenesis and matrix metalloproteinase-2 immunoexpression in wound repair. Issue 1 (January 2017) - Medeiros, Melyssa; Araújo-Filho, Irami; Silva, Efigênia; Sousa Queiroz, Wennye; Soares, Ciro; Carvalho, Maria; Maciel, Maria
Abstract Low-level laser therapy (LLLT) induces anti-inflammatory and angiogenic activities in wound healing. However, the mechanism of action and optimal parameters require further clarification. In this study, we investigated the effects of LLLT on wound healing matrix metalloproteinase (MMP)-2 immunoexpression and angiogenic processes. Twenty female Wistar rats were randomly divided into four groups (n  = 5) according to the treatments as follows. CG7 and CG14 were control groups at days 7 and 14, respectively, which received physiological saline (0.9 % NaCl daily). LG7 and LG14 were laser therapy groups at days 7 and 14, respectively, which received two (LG7) or four (LG14) LLLT applications (40 mW; 660 nm; 4 J/cm2 ). A dorsal skin sample in the wound area (measuring 2 cm2 ) was removed after the experimental period, and then the animals were euthanized. The specimens were processed for qualitative and quantitative histological analyses and measurement of MMP-2 expression in the dermis and epidermis. A persistent crust and moderate number of inflammatory cells were found in CG7 and CG14 groups. In the LG14 group, wounds demonstrated complete re-epithelization at the remodeling phase. Angiogenesis and MMP-2 expression were higher in LLLT-treated groups, particularly the LG14 group, which correlated according to the Spearman correlation test. LLLT improves wound healing by enhancing neocollagenesis, increasing the amount of new vessels formed in the tissue (neoangiogenesis), and modulating MMP-2 expression. Epidermal overexpression of MMP-2 was correlated to angiogenic processes.